A missing meal of reconciliation: The consumption of food as deficient motif in the Joseph story and its resolution in Jubilees and Josephus - Rabel, Magnus (Journal for the study of the pseudepigrapha, 2024)
Food plays an important role in the Joseph story. Although other themes offer valuable insights as well, the theme of table fellowship is at the heart of the story’s main theme because sharing a table and what is on it shows mutual recognition and signifies thus much more than the mere consumption of food. In the Joseph story, we have two occurrences of joint meals: Gen 37:25 and Gen 43:31–34. Whereas the first is a clear sign of Joseph’s isolation and the rupture of the brothers’ relationship, the second meal cannot be understood as an actual meal of reconciliation as some do. In order to make table fellowship a coherent theme from isolation to inclusion, the Joseph story in Genesis lacks a third meal of peace and reconciliation at which the brothers are reunited. However, if we look across canonical boundaries, we find that Jubilees as well as Josephus’s Antiquities incorporate this third meal into the story. In this way, the biblical story is continued productively, and the theme of table fellowship, which is anticipated in Genesis, is expanded into a comprehensive motif.